Pengaruh Teknologi Informasi dan Telekomunikasi terhadap Perubahan Cuaca di Indonesia - Misdianto, Mokhammad (LPPM of STIMIK ESQ, 2015)
Climate change is happened all over the glove, including here in Indonesia. Information and communication technology are grow very fast and changing the way we life in this planet earth. The correlation between both was studied in some places to increase the living condition. It is also helping the human being in preparation for facing the resilience of climate change that happened now.